2017
DOI: 10.1039/c7qo00122c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic investigation of Rh(i)-catalyzed alkyne–isatin decarbonylative coupling

Abstract: Theoretical studies reveal the ligand role in the Rh(i)-catalyzed alkyne–isatin decarbonylative coupling and account for the origin of chemo- and region-selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…In the first part of the text we consider the formation of a hydride species from [Ir­(emim)­(η 4 -COD)­(PPh 3 )] + ( 1 ), where the PPh 3 is used instead of m tppts. To find the active form of the catalyst, the displacement of the COD ligand needs to be considered as well, as the catalytic activity of iridium complexes in alkene hydrogenation is well-known. , Also, because formate insertion ( 3 ) is endergonic, the hydrogenation of COD to cyclooctene is required to precede this process, as shown in Figure . For the reaction of COD + 2H 2 = cyclooctane, Δ G is −33.1 kcal mol –1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the first part of the text we consider the formation of a hydride species from [Ir­(emim)­(η 4 -COD)­(PPh 3 )] + ( 1 ), where the PPh 3 is used instead of m tppts. To find the active form of the catalyst, the displacement of the COD ligand needs to be considered as well, as the catalytic activity of iridium complexes in alkene hydrogenation is well-known. , Also, because formate insertion ( 3 ) is endergonic, the hydrogenation of COD to cyclooctene is required to precede this process, as shown in Figure . For the reaction of COD + 2H 2 = cyclooctane, Δ G is −33.1 kcal mol –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the development of an enantioselective decarbonylative process, which would lead to new types of asymmetric transformations, is also highly desirable. Finally, recent trends have focused on the use of DFT calculations to understand the decarbonylative process, , especially for the decarbonylation and transmetalation sequence in cross-coupling. Elegant computational studies on esters, amides, ,, acyl fluorides, , and in situ anhydrides ,, have been reported.…”
Section: Discussionmentioning
confidence: 99%